Teaching Factory-Based Entrepreneurship Learning in Vocational High Schools: A Multi-Site Study of School-Industry Collaboration - Lis Parida; Sudarwan Danim; Rendy Wikrama Wardana; Eko Risdianto (Berkala Ilmiah Pendidikan, 2026)
This study examines how entrepreneurship learning in vocational high schools is implemented through collaboration between schools and business and industry partners based on the Teaching Factory model. Using a qualitative multi-site design, the research was conducted in 16 vocational high schools across South Sumatra. Data were collected through observation, semi-structured interviews, and document analysis involving principals, curriculum or industry-relations vice principals, Teaching Factory coordinators, entrepreneurship teachers, productive teachers, industry partners, and students. The findings show that entrepreneurship learning within Teaching Factory is not merely a technical production practice but a learning system that connects school policy, curriculum integration, teacher roles, industry involvement, and students’ learning experiences. The depth of school-industry collaboration shapes the quality of students’ entrepreneurial learning, especially in developing discipline, responsibility, initiative, teamwork, self-confidence, and business orientation. Strong implementation is supported by leadership commitment, teacher collaboration, production units, and substantive partner involvement, while limited facilities, uneven industry participation, unstable practice schedules, and weak administration remain constraints. The study concludes that Teaching Factory should be positioned as an entrepreneurial learning ecosystem in vocational education.